Can a Single Representational Object Account for Different Number-Space Mappings? - Viarouge, Arnaud; de Hevia, Maria Dolores (Frontiers in Human Neuroscience, 2021)
Numbers are mapped onto space from birth on, as evidenced by a variety of interactions between the processing of numerical and spatial information. Two main types of number/space mappings have been reported : number/location and number/spatial extent mappings. Both mappings are usually assumed to reflect the fact that numbers are represented on an internal continuum, the mental number line. However, to date there is very little evidence that these two mappings actually reflect a single representational object. Across two experiments in adults, we investigated the interaction between number/location and number/spatial extent congruency effects, both when numbers were presented in a non-symbolic and in a symbolic format. We observed a significant interaction between the two mappings, but only in the context of an implicit numerical task. The results were unaffected by the format of presentation of numbers. We conclude that the number/location and the number/spatial extent mappings can stem from the activation of a single representational object, but only in specific experimental contexts.